Keluarnya Amerika Serikat dari Kesepakatan the Joint Comprehensive Plan of Action (JCPOA) - Krismayanti, Riska Violina; Iqbal, Muhammad; Prabhawati, Adhiningasih (University of Jember, 2022)
The P5+1 countries (United States, France, Britain, Russia, China, and Germany) with Iran formed a nuclear agreement called the Joint Comprehensive Plan of Action (JCPOA) in 2015. The JCPOA has the goal of limiting Iran's nuclear activities only as a technological development activity, not for nuclear weapons purposed. When the United States was under Donald Trump's administration, he stated that the United States should withdraw from JCPOA. The decision was created from his consideration as president at the time of the JCPOA applied. Rational choice theory and game theory are used to analyze Donald Trump's decision. Donald Trump views that the JCPOA does not have a major influence in stopping Iran's nuclear activities entirely. In addition, Iran's political and economic influence at the time the JCPOA took effect became a threat to the United States. Moreover, JCPOA is also not beneficial for the United States from Donald Trump’s point of view. Keywords: United States, Donald Trump, JCPOA